PS 16-07 BROWNING ADIPOCYTE IS HIGHLY OBSERVED IN MICE WITH LACKING OF ANGIOTENSIN II TYPE 1 RECEPTOR. (September 2016) - Mogi, Masaki; Tsukuda, Kana; Iwanami, Jun; Kan-no, Harumi; Bai, Hui-Yu; Shan, Bao-Shuai; Kukida, Masayoshi; Yamauchi, Toshifumi; Higaki, Akinori; Min, Li-Juan; Horiuchi, Masatsugu
Abstract: Objective: Browning of white adipose tissue (WAT) has been highlighted as a new possible therapeutic target for obesity, diabetes and lipid metabolic disorders, because WAT browning could increase energy expenditure and reduce adiposity. The new clusters of adipocytes emerged with WAT browning have been named 'beige' or 'bright' adipocytes. Recent reports have indicated that renin-angiotensin system (RAS) play a role in various aspects of adipose tissue physiology and dysfunction. The biological effects of angiotensin II, a major component of RAS, are mediated by two receptor subtypes, angiotensin II type 1 receptor (AT1 R) and type 2 receptor (AT2 R). However, the functional roles of angiotensin II receptor subtypes in WAT browning have not been defined. Therefore, we examined whether deletion of angiotensin II receptor subtypes (AT1a R and AT2 R) may affect white-to-beige fat conversion in vivo. Design and method: For in vivo analysis, male 10 week-old C57BL/6J mice (WT), AT1a receptor-deficient mice (AT1a KO) and AT2 receptor-deficient mice (AT2 KO) mice were used in this study. For in vitro analysis, adipose tissue-derived stem cells (ASCs) were isolated from inguinal-subcutaneous WAT from each mouse. Expression of mRNA was investigated by RT- PCR methods. Adipocyte differentiation was evaluated by morphological analysis and Oil Red O staining. Results: AT1a KO exhibited increased appearance of multilocular lipid droplet and upregulation of thermogenic gene expressions in inguinal white adipose tissues (iWATs) compared to wild-type (WT) mice. AT2 KO did not show miniaturization of lipid droplet and alteration of thermogenic gene expression levels in iWAT. In vitro experiment using ASCs showed that the deletion of AT1a receptor resulted in suppression of adipocyte differentiation with reduction in expression of thermogenic genes. Conclusions: These results indicate that deletion of AT1a receptor might have some effects on the process of increasing browning of WAT and indicate that blockade of AT1 receptor could be a therapeutic target for the treatment of metabolic disorders.